Students Interest in Speaking Instruction through Describing Object Method at Junior High School - Amardiaz, Rifky; Dalimunte, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to explore the process of teaching speaking through the describing object method at Istiqlal Junior High School, Deli Serdang, North Sumatra. The research method used a quantitative method. Junior High School. In collecting data, the researcher used participatory observation to record the teaching and learning process. The researcher used an observation sheet with Likert scale to measure the effectiveness of the process. The researcher examined using a Likert scale for students' speaking in the agree category across five aspects. Most students strongly agree that they are satisfied with speaking (84%), interaction (81%), motivation to speak (72%), confidence (85%), and liking to speak (87%). Overall, interest students' speaking reached a percentage of 87% strongly agreeing to have an interest in learning to speak by using the describing object method. Based on data analysis, it showed that students gave positive responses, which shows that this method not only speaks to friends but also builds their confidence. The use of the describing object method with a single picture is recommended as an effective learning strategy for students' speaking skills in English class.